2021
DOI: 10.1002/smll.202007245
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Nature of Pt Single‐Atom Catalyst during Electrocatalytic Hydrogen Evolution and Oxygen Reduction Reactions

Abstract: Single-atom catalysts (SACs) have attracted significant attention due to their superior catalytic activity and selectivity. However, the nature of active sites of SACs under realistic reaction conditions is ambiguous. In this work, high loading Pt single atoms on graphitic carbon nitride (g-C 3 N 4)-derived N-doped carbon nanosheets (Pt 1 /NCNS) is achieved through atomic layer deposition. Operando X-ray absorption spectroscopy (XAS) is performed on Pt single atoms and nanoparticles (NPs) in both the hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 36 publications
(46 reference statements)
1
72
0
Order By: Relevance
“…2 ) and XAS results (Supplementary Fig. 3 ) 36 . The loading of Pt is as high as 2.0 wt% based on the inductively coupled plasma optical emission spectrometer (ICP-OES) results.…”
Section: Resultsmentioning
confidence: 89%
“…2 ) and XAS results (Supplementary Fig. 3 ) 36 . The loading of Pt is as high as 2.0 wt% based on the inductively coupled plasma optical emission spectrometer (ICP-OES) results.…”
Section: Resultsmentioning
confidence: 89%
“…SACs consist of metal atoms individually fastened on a specific support, mostly doping-induced graphene materials. 97,98 The coordinating atom and the singly occupied metal sites create active centers for catalysis. The most attractive feature of SACs is their efficiency in the utilization of 100% of their metal centers to be active towards any catalytic application.…”
Section: Single-atom Electrocatalysts (Sacs)mentioning
confidence: 99%
“…It has been demonstrated that ideal electrocatalysts for the hydrogen evolution reaction (HER) are the Pt-group noble metals, which own the advantages of high intrinsic activity, low catalytic barrier, and excellent stability. However, the scarcity and expensive price limit their widespread applications. Therefore, developing alternative electrocatalysts with outstanding HER catalytic performance and abundant reserve is quite desirable and indispensable.…”
Section: Introductionmentioning
confidence: 99%